The Role of PGE2 in Alveolar Epithelial and Lung Microvascular Endothelial Crosstalk - Thomas Bärnthaler (Nature Portfolio, 2017)
Abstract Disruption of the blood-air barrier, which is formed by lung microvascular endothelial and alveolar epithelial cells, is a hallmark of acute lung injury. It was shown that alveolar epithelial cells release an unidentified soluble factor that enhances the barrier function of lung microvascular endothelial cells. In this study we reveal that primarily prostaglandin (PG) E2 accounts for this endothelial barrier-promoting activity. Conditioned media from alveolar epithelial cells (primary ATI-like cells) collected from BALB/c mice and A549 cells increased the electrical resistance of pulmonary human microvascular endothelial cells, respectively. This effect was reversed by pretreating alveolar epithelial cells with a cyclooxygenase-2 inhibitor or by blockade of EP4 receptors on endothelial cells, and in A549 cells also by blocking the sphingosine-1-phosphate1 receptor. Cyclooxygenase-2 was constitutively expressed in A549 cells and in primary ATI-like cells, and was upregulated by lipopolysaccharide treatment. This was accompanied by enhanced PGE2 secretion into conditioned media. Therefore, we conclude that epithelium-derived PGE2 is a key regulator of endothelial barrier integrity via EP4 receptors under physiologic and inflammatory conditions. Given that pharmacologic treatment options are still unavailable for diseases with compromised air-blood barrier, like acute lung injury, our data thus support the therapeutic potential of selective EP4 receptor agonists.